REFORMULATION OF THE ISLAMIC EDUCATION PHILOSOPHY; A Study of the Epistemological Thought of al-Farabi - Nani Widiawati (Fakultas Agama Islam Universitas Wiralodra, 2019)
Philosophy that works as the basis for the development of science, must be relevant to the area of scientific ontological it builds. This relevance problem is still a problem in Islamic scientific building, among others, in the Islamic Education Philosophy which seem difficult to escape from the dominance of positivism. The aim of this paper to describe the structure of the epistemology of al-Farabi which will be the basis of the reformulation of the Islamic Education Philosophy paradigm. The study used an analitical-interpretative method with the content analysis technique of works related to al-Farabi’s thought. On the ontological aspect, the reformulation of the Islamic Education Philosophy paradigm should be rationally connected between the material available in the curriculum. In the epistemological aspect, education is expected to show the process of forming students who are able to apply knowledge into their attitudes and actions. In practical areas, education operate in the area of “moral” manifested, among others, because of the exemplary factor of teacher whose theoretical knowledge has been subjectivated.